The effect of four weeks high-intensity interval training (HIIT) on the content of AKT1, mTOR, P70S6K1, 4EBP1 proteins in the Left ventricular muscle tissue of the heart obese rats with type 2 diabetic - Neda Aghaei Bahman Beglou; saeedeh shadmehri; Shiva Jahani Golbar; Mohammad Sharafati Moghadam (Shahid Beheshti University, 2021)
Purpose: The pathway for a Rapamycin target in mammals (mTORC1) is one of the important pathways for protein synthesis in the heart, and diabetes can lead to disorder of this pathway. The aim of this study was to investigate the effect of four weeks high-intensity interval training (HIIT) on the content of AKT1, mTOR, P70S6K1, 4EBP1 proteins in the left ventricular muscle tissue of the heart obese rats with type 2 diabetic.Methods: In this experimental study, 16 Sprague-Dawley male rats (with mean weight of 300 ± 20 gr) were selected and after induction of diabetes by STZ and nicotinamide was randomly assigned into two groups: diabetic training and diabetic control. The experimental group performed HIIT training for four weeks' accordance with the training program for four weeks, while the control group did not have any training program. Independent t-test was used to analyze the data.Results:  There was no significant difference change the total form content of the AKT1 proteins (p=0.56), mTOR (p=0.50), P70S6K1 (p=0.99) and 4E-BP1 (p=0.32) in the training group compared to the control group; Also, the HIIT training did not significantly changed the phosphorylated form content of AKT1ser473 (p=0.25), mTORser2448 (p=0.74), P70S6K1Thr389 (p=0.37) and 4E-BP1Thr37/46 (p=0.38) proteins in the training group compared to the control group.Conclusion: HIIT training has not significantly changed the total and phosphorylated form content of the AKT1, mTOR, P70S6K1, 4EBP1 proteins in the left ventricle of heart tissue obese rats with type 2 diabetic.